Epidemiological Association Between Long-Term Fine Particulate Matter Exposure and Cardiovascular Disease: A Systematic Review and Meta-Analysis (Nepal Journal of Epidemiology, 2025)
Background: Air pollution and particularly the fine particulate matter (PM2.5) is a major environmental risk factor of cardiovascular diseases (CVD). Millions of untimely deaths every year have been reported because of it. The epidemiological literature has linked long-term exposure to PM2.5 and mortality rates of CVDs. This meta-analysis aims to synthesize the estimates of long-term PM2.5 exposure and CVDs.Methods: Based on the PRISMA guidelines, PubMed, Embase, Web of Science, and Scopus were searched up to October 2025. Random-effects model was used to pool HRs, and the heterogeneity was measured with the help of I².Results: Four studies were included in this meta-analysis. There was an increased incidence of CVD with higher exposure to PM2.5 on a long-term basis (pooled HR=1.22, 95% CI: 1.06–1.41; p=0.006; I²=96%). CVD mortality did not show any significant association with PM2.5 exposure (pooled HR=1.00, 95% CI: 0.71–1.41; p=0.98; I²=29%). No significant difference was found between the PM2.5 exposure and ischemic heart disease (IHD) (pooled HR=1.65, 95% CI: 0.90–3.00; p=0.10; I²=95%). The Same pattern was noted between the PM2.5 exposure and stroke (pooled HR=1.61, 95% CI: 0.96–2.68; p=0.07; I²=74%).Conclusion: The PM2.5 exposure is associated with high CVD in the long term.  Results reveal the significance of establishing strict air-drome quality standards and targeted interventions to mitigate the risks in the areas of issues. More integrated studies are required to support our findings and fill the knowledge gap.